Prevalence of Mild-Cognitive-Impairment and Depression among Elderly Clients in Selected Wards of Baraha Municipality: A Cross-Sectional Study - Pradhan, Nirmala; Adhikari, Baikuntha Raj; Lama, Sami; Shrestha, Sharmila; Sigdel, Rambha (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Mild-Cognitive-Impairment (MCI) is an intermediate state between normal cognitive ageing and dementia. Identification of MCI is thought to be crucial to early intervention. Objectives: To assess Mild-Cognitive-Impairment and Depression among elderly clients and to find out the associations between Mild-Cognitive-Impairment and Depression and socio-demographic variables. Methods: A descriptive, cross-sectional study design was adopted. A total of 115 elderly clients who fulfilled the selection criteria were enrolled using purposive sampling technique. Montreal Cognitive Assessment (MoCA) and Geriatric Depression Scale were used with Interview technique. Those elderly clients were selected from the 2 wards of Baraha Municipality. Results: Majority of the subjects (68.7%) were from between 60-70 years. More of the elderly clients were females (54.8%). Maximum (81.7%) were illiterate. About 35.7% had the history of medical and psychiatric illness. From the total sample, 39.1% had issues with memory. In case of Montreal Cognitive Assessment (MoCA), 93.0% was screened with Mild-Cognitive-Impairment. And, 60.9%of the elderly clients were screened as Depression. With regard to the associations between mild cognitive impairment and selected demographic variables, significant associations were found with gender, education level, marital status and previous history of medical/ psychiatric history. The correlation between MoCA score and geriatric depression score showed a negative relationship. Conclusion: Many elderly people in a community have Mild-Cognitive-Impairment and Depression. This study added evidence on prevalence of Mild-Cognitive-Impairment and Depression among geriatric clients in a community-dwelling.